ANALISIS PERJANJIAN MENGENAI BIAYA TAMBAHAN PADA SHOPEE PINJAM MENURUT KETENTUAN FATWA DSN-MUI - Della Khairunnisa; Syahbudi Syahbudi; Nanda Himmatul Ulya (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2023)
This research is motivated by the existence of various additional fees in Shopee Pinjam (SPinjam), but with regard to the meaning of this additional fee, several scholars do not agree on the exact meaning of this additional fee. Therefore, the researcher wants to examine the meaning of additional fees in Shopee Pinjam from the perspective of the fatwa of the National Sharia Council-Majelis Ulama Indonesia whether it is contradictory or not. This research employs normative and empirical research methods. The results of this study indicate that: 1) SPinjamm users know the amount of additional fees from the beginning. The additional fees in SPinjam are a 5% installment fee, a 1% disbursement fee, a 0.3% SPinjam protection fee, and a 5% late fee. These additional fees are not a burden to users. The additional fees charged in SPinjam can relieve the lender party and can provide prudence to the borrowers so that they are disciplined and not negligent in paying loans. 2) The additional fees in SPinjam are not among the additional fees prohibited in the fatwa of DSN-MUI because these additional fees are part of the improvement and maintenance of the company's systems and facilities. Moreover, this additional fee in SPinjam is in accordance with the general provisions of Fatwa DSN-MUI No. 117/DSN-MUI/2018 in point 5 of the general provisions and Fatwa DSN-MUI No. 19/DSN-MUI/IV/2001 in point 3 of the general provisions.